2012
DOI: 10.1186/1471-244x-12-220
|View full text |Cite
|
Sign up to set email alerts
|

Selective acquired long QT syndrome (saLQTS) upon risperidone treatment

Abstract: BackgroundNumerous structurally unrelated drugs, including antipsychotics, can prolong QT interval and trigger the acquired long QT syndrome (aLQTS). All of them are thought to act at the level of KCNH2, a subunit of the potassium channel. Although the QT-prolonging drugs are proscribed in the subjects with aLQTS, the individual response to diverse QT-prolonging drugs may vary substantially.Case presentationWe report here a case of aLQTS in response to small doses of risperidone that was confirmed at three ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Among atypical agents, risperidone had a similar cardiac safety profile to olanzapine; whereas, quetiapine was associated with lower risk compared to olanzapine. A case report of low-dose risperidone-induced long QT, confirmed on three independent drug challenges, was described [ 124 ] (Table 4 ). There are no reported cases of lithium induced TdP.…”
Section: Non-antiarrhythmic Drugs Associated With Increased Risk Of Tmentioning
confidence: 99%
“…Among atypical agents, risperidone had a similar cardiac safety profile to olanzapine; whereas, quetiapine was associated with lower risk compared to olanzapine. A case report of low-dose risperidone-induced long QT, confirmed on three independent drug challenges, was described [ 124 ] (Table 4 ). There are no reported cases of lithium induced TdP.…”
Section: Non-antiarrhythmic Drugs Associated With Increased Risk Of Tmentioning
confidence: 99%
“…The effect of clozapine on QTc interval was described in 1 systematic review, 59 13 studies, 33 , 45 , 50 , 51 , 55 , 61 , 67 , 77–82 and 6 case reports. 71 , 73 , 83–86 One study found no significant change from baseline in mean QTc interval or the incidence of QTc prolongation, 79 but this is inconsistent with findings from other researchers. Four studies of 4951 psychiatric inpatients have reported an increased risk of QTc prolongation with clozapine (odds ratios, 1.006 [95% CI, 1.003–1.008] and 2.4 [95% CI, 1.4–4.2]), with the magnitude of effect being dose dependent ( Table 3 ).…”
Section: Antipsychoticsmentioning
confidence: 92%
“…Aripiprazole discontinued and QTc normalized (450 ms) after 14 days Vieweg et al 2013 130 28–87 Male (n = 4)/female (n = 9) Various Various All cases had QTc prolongation with APs in the absence of overdose. Risk factors for QTc prolongation: risperidone, female sex, older age, heart disease, hypokalemia, bradycardia, liver disease, QTc-prolonging drugs (other than risperidone), and metabolic inhibitors Lazarczyk et al 2012 71 37 Female Schizophrenia Aripiprazole: 20 mg/d Haloperidol: 3 mg/d Escitalopram: 20 mg/d Benzodiazepines: dose NR Addition of risperidone 1–2 mg/d increased QTc interval from 458 to 508 ms. Prolongation remained despite discontinuation of potential QTc-prolonging drugs. Administration of other APs, including clozapine, did not affect QTc Cohen et al 2001 83 30 Male Schizophrenia Clozapine: 500 mg/d QTc with clozapine 500 mg/d (monotherapy): 624 ms. QTc with olanzapine 10 mg/d + valproic acid 1800 mg/d: 504 ms Aripiprazole Karz et al 2015 70 80 Female Schizoaffective disorder, bipolar type Aripiprazole: 10 mg/d Fluoxetine: 20 mg/d Lisinopril: 5 mg/d Simvastatin: 10 mg/d Aspirin: 81 mg/d Aripiprazole was discontinued post-MI.…”
Section: Literature Searchmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic susceptibility, namely, mutations in the genes encoding potassium ion channel proteins ( i.e. , KCNH2 , KCNQ1 , and SCN5A ) is also directly associated with an increased risk of malignant arrhythmias[ 94 ]. In addition to the inherited hERG mutations that are associated with congenital long QT syndrome, suppression of native I Kr by psychotropic therapy also predisposes individuals to polymorphic ventricular tachycardia of the TdP type[ 95 ].…”
Section: Mechanisms Underlying Antipsychotics Cardiotoxicitymentioning
confidence: 99%